Plan de Negocios para Estudio de Factibilidad de Creación de un Restaurante de Comida especializada para Diabéticos en la ciudad de Santa Marta (2021)
This document contains the feasibility study for the analysis of the components that affect the success of a business option, specifically a restaurant specialized in healthy meals, to meet the nutritional demand of people with diabetes disease in the city of Santa Marta. For this, an analysis of the economic factors is made to evaluate the business proposal and the theoretical concepts related to the nutrition of the diabetic population in the city of Santa Marta. Additionally, guidance is provided on how to lead a healthy life through food, both for people who already suffer from this disease and for those who want to have a healthy diet.